2007
DOI: 10.1007/s00424-007-0369-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fast and slow alkali myosin light chain isoforms on the kinetics of stretch-induced force transients of fast-twitch type IIA fibres of rat

Abstract: This study contributes to understand the physiological role of slow myosin light chain isoforms in fast-twitch type IIA fibres of skeletal muscle. These isoforms are often attached to the myosin necks of rat type IIA fibres, whereby the slow alkali myosin light chain isoform MLC1s is much more frequent and abundant than the slow regulatory myosin light chain isoform MLC2s. In the present study, single-skinned rat type IIA fibres were maximally Ca(2+) activated and subjected to stepwise stretches for causing a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…We evaluated this possibility in MHC IIA fibres since a more robust relationship between MLC composition and single fibre function has been observed in MHC II fibres (Bottinelli et al 1994) compared to MHC I (Reiser & Bicer, 2006). In agreement with prior work (Billeter et al 1981), only the MLC 1f, MLC 2f and MLC 3 isoforms were found in MHC IIA fibres, suggesting that differences in cross‐bridge kinetics cannot be explained by the expression of slow MLC isoforms (Andruchov & Galler, 2008). Additionally, no differences in MLC distribution between heart failure patients and controls were found and no correlation was observed between essential MLC composition and t on (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We evaluated this possibility in MHC IIA fibres since a more robust relationship between MLC composition and single fibre function has been observed in MHC II fibres (Bottinelli et al 1994) compared to MHC I (Reiser & Bicer, 2006). In agreement with prior work (Billeter et al 1981), only the MLC 1f, MLC 2f and MLC 3 isoforms were found in MHC IIA fibres, suggesting that differences in cross‐bridge kinetics cannot be explained by the expression of slow MLC isoforms (Andruchov & Galler, 2008). Additionally, no differences in MLC distribution between heart failure patients and controls were found and no correlation was observed between essential MLC composition and t on (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…We examined changes in myosin light chain (MLC) composition, which has been shown to modulate single fibre function and kinetics (Bottinelli et al 1994; Andruchov & Galler, 2008), as a possible explanation for increased t on with heart failure. We evaluated this possibility in MHC IIA fibres since a more robust relationship between MLC composition and single fibre function has been observed in MHC II fibres (Bottinelli et al 1994) compared to MHC I (Reiser & Bicer, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The authors demonstrated that the long ELC (MLC1) may contribute to a slower shortening velocity suggesting that the removal of the N-terminal ELC extension would result in a faster cross-bridge kinetics. A recent study by Andruchov et al 44 however showed no effect of the MLC1/MLC3 ratio on the kinetics of force transients. Our data are in line with the latter study 45.…”
Section: Discussionmentioning
confidence: 88%
“…A recent study by Andruchov et al 44 however showed no effect of the MLC1/MLC3 ratio on the kinetics of force transients. Our data are in line with the latter study 45. Nevertheless, the regulation of the myosin cross-bridge kinetics by the N-terminal ELC extension in cardiac muscle contraction is still an open question and perhaps the employment of a single molecule approach, e.g.…”
Section: Discussionmentioning
confidence: 88%
“…It is found that myosin light chain protein could be phosphorylated and activated by its kinase [23]. The myosin light chain protein regulates multiple processes that are involved in material transport, muscle shrink and cell division [24,25]. The gene structure, organization and evolution of the myosin light chains has been intensively studied in mammalian, avian specie [18].…”
Section: Introductionmentioning
confidence: 99%